(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is enzootic throughout the Middle East. In Israel rabies is endemic and stray dogs (Canis familiaris) form the main reservoir and transmitter. Since 2004 and to the present the state of Israel has been forced to cope with a rabies strain new to the country, designated V7. Because dogs are in close contact with people the new V7 strain that circulated at the Northern region of Israel possesses a serious health threat to humans. In the present communication we report a tourism type of rabies translocation, in which a family from Jerusalem took their unvaccinated dog to the northern Israel. On 19 December, 2011 a dog was diagnosed positive for rabies in the Israeli National Rabies Laboratory at the Kimron Veterinary Institute. A case investigation revealed that on 13 December, a 3 years old Golden Retriever dog belonging to a family living in Jerusalem showed clinical symptoms of inappetence, salivation and incoordination. The dog was vaccinated twice against distemper and parvo virus Duramune Max® (Fort Dodge, Iowa, USA) but not against rabies. On 15 December the dog was admitted to a private veterinary clinic in Jerusalem and under clinical examination it showed unusually alert behaviour and reaction to external stimuli. The dog showed no clinical symptoms of aggression during the period of illness. On 16 December the dog showed ulterior deterioration of clinical symptoms with convulsions and unconsciousness and was treated with diazepam (Assival, Teva). As no health improvement was seen, the dog was euthanized on 18 December and was transferred to the Kimron Veterinary Institute. Rabies was diagnosed by direct fluorescence assay, and was confirmed by isolation of the rabies virus in tissue culture and its inoculation into a family of suckling mice. Reverse transcriptase – PCR and direct sequencing were applied to a 469 base pair (bp) G-L intergenic region fragment and to the entire 1350 bp of the nucleoprotein gene . A phylogenetic tree showed that the Jerusalem dog’s sequence belonged to the V7 genetic variant that circulated in northern Israel. During the period of 2004 to 2011, 181 rabies viruses belonging to V7 genetic variants were isolated from rabid animals in northern Israel. The Jerusalem dog’s rabies virus isolate was the only example of the V7 genetic variant that was ever isolated from an animal in Central Israel. The Jerusalem dog was probably bitten by the rabid stray dog that circulated on the eastern coast of the Lake Kinneret located in Northern Israel. After an incubation period of about 2 months the clinical symptoms appeared in Jerusalem. As a consequence of this rabies diagnosis, post-exposure vaccination was given to the two owners, two veterinarians and an additional 18 people, who had come into contact with the dog in Jerusalem. Various sanitary measures were imposed in Jerusalem, such as reinforcement of measures against stray animals, boosting of domestic dog vaccination and quarantine of unvaccinated dogs. Because domestic animals can serve as a bridge between wildlife rabies reservoirs and humans, their vaccination greatly effective as public health tools that are available to safeguard the human health.